A Case of Cheilitis Granulomatosa/Orofacial Granulomatosis - Brown R; Farquharson A; Cherry-Peppers G; Lawrence L; Grant-Mills D (Dove Medical Press, 2020)
Ronald Brown,1 Andre Farquharson,1 Gail Cherry-Peppers,2 Leslie Lawrence,3 Donna Grant-Mills2 1Department of Oral Diagnosis & Radiology, Howard University College of Dentistry, Washington, DC, USA; 2Department of Restorative Dentistry, Howard University College of Dentistry, Washington, DC, USA; 3Department of Pediatric Dentistry, Howard University College of Dentistry, Washington, DC, USACorrespondence: Ronald BrownDepartment of Oral Diagnosis & Radiology, Howard University College of Dentistry, 600 W Street, NW, Washington, DC 20059, USATel +1 202-806-0020Email rbrown@howard.eduAbstract: A case of a 19-year-old female patient is presented to a private practice dental clinician with swelling of the lower lip and inflammation of the anterior dorsal tongue. The patient presented with moderate oral pain as well as abdominal pain. The lesions were biopsied and noted for a granulomatous histopathologic appearance. The patient reported a history of using cinnamon as a flavoring agent. The lesions resolved within two weeks after the biopsy procedures and topical steroid therapy. The lesions were diagnosed as cheilitis granulomatosa/orofacial granulomatosis. The patient has remained lesion free as of the three-year follow-up. Etiologic, diagnostic and therapeutic issues related to this relatively rare condition of cheilitis granulomatosa/orofacial granulomatosis are discussed.Keywords: cheilitis granulomatosa, orofacial granulomatosis, cinnamon